Locus specific endogenous retroviral expression associated with Alzheimer’s disease - Tyson Dawson; Tyson Dawson; Uzma Rentia; Jessie Sanford; Carlos Cruchaga; John S. K. Kauwe; Keith A. Crandall; Keith A. Crandall (Frontiers in Aging Neuroscience, 2023)
IntroductionHuman endogenous retroviruses (HERVs) are transcriptionally-active remnants of ancient retroviral infections that may play a role in Alzheimer’s disease.MethodsWe combined two, publicly available RNA-Seq datasets with a third, novel dataset for a total cohort of 103 patients with Alzheimer’s disease and 45 healthy controls. We use telescope to perform HERV quantification for these samples and simultaneously perform gene expression analysis.ResultsWe identify differentially expressed genes and differentially expressed HERVs in Alzheimer’s disease patients. Differentially expressed HERVs are scattered throughout the genome; many of them are members of the HERV-K superfamily. A number of HERVs are correlated with the expression of dysregulated genes in Alzheimer’s and are physically proximal to genes which drive disease pathways.DiscussionDysregulated expression of ancient retroviral insertions in the human genome are present in Alzheimer’s disease and show localization patterns that may explain how these elements drive pathogenic gene expression.